Water-Assisted Electron-Induced Chemistry of the Nanofabrication Precursor Iron Pentacarbonyl - Lengyel, Jozef; Pysanenko, Andriy; Swiderek, Petra; Heiz, Ueli; Fárník, Michal; Fedor, Juraj (The journal of physical chemistry. A, 2021)
Focused electron beam deposition often requires the use of purification techniques to increase the metal content of the respective deposit. One of the promising methods is adding H2O vapor as a reactive agent during the electron irradiation. However, various contrary effects of such addition have been reported depending on the experimental condition. We probe the elementary electron-induced processes that are operative in a heterogeneous system consisting of iron pentacarbonyl as an organometallic precursor and water. We use an electron beam of controlled energy that interacts with free mixed Fe(CO)5/H2O clusters. These mimic the heterogeneous system and, at the same time, allow direct mass spectrometric analysis of the reaction products. The anionic decomposition pathways are initiated by dissociative electron attachment (DEA), either to Fe(CO)5 or to H2O. The former one proceeds mainly at low electron energies (<3 eV). Comparison of nonhydrated and hydrated conditions reveals that the presence of water actually stabilizes the ligands against dissociation. The latter one proceeds at higher electron energies (>6 eV), where the DEA to H2O forms OH- in the first reaction step. This intermediate reacts with Fe(CO)5, leading to enhanced decomposition, with the desorption of up to three CO ligands. The present results demonstrate that the water action on Fe(CO)5 decomposition is sensitive to the involved electron energy range and depends on the hydration degree.